Long-term effects of symphyseal distraction and rapid maxillary expansion on pharyngeal airway dimensions, tongue, and hyoid position - (:unkn) unknown (MOSBY-ELSEVIER, 2007)
Introduction: The aim of this study was to evaluate the effects of mandibular symphyseal distraction osteogenesis (MSDO) followed by rapid maxillary expansion (RME) on the pharyngeal and nasal airway dimensions and the tongue and hyoid positions. Methods: The material consisted of lateral and posteroanterior cephalometric radiographs of 13 female and 7 male patients (mean age, 20.0 +/- 2.3 years). Records were taken before treatment, after distraction (11.4 +/- 2.2 days after surgery), after RME (94.9 +/- 5.8 days after surgery), and at follow-up appointments (24.1 +/- 4.2 months after surgery). MSDO was performed with a custom-made tooth-and-bone-borne device. RME was performed with an acrylic bonded device. The average amounts of mandibular and maxillary expansion were 8.1 +/- 1.7 and 5.9 +/- 1.0 mm, respectively. Results: Posteroanterior cephalometric analysis showed significant transversal width increases between the mandibular canines and molars. No significant pharyngeal or transverse nasal airway changes occurred with MSDO except for a significant decrease in tongue length. However, MSDO followed by RME caused statistically significant but clinically small changes in oropharyngeal width (+1.0 mm), tongue length (-2.2 mm), vertical airway length (-2.3 mm), and vertical position of the hyoid bone (-1.4 mm), which were all stable at the 2-year follow-up. Conclusions: The results suggest that MSDO alone or MSDO followed by RME does not significantly affect the pharyngeal airway dimensions or the hyoid position in adults. Any changes caused by these procedures might have been counteracted by the reflex mechanisms that protect airway potency.
Keywords: BONE POSITION; HEAD POSTURE; NASAL; OSTEOGENESIS; RESISTANCE; OSTEOTOMY; SKELETAL; ADULTS